KONSTRUKSI BERITA KONFLIK KPK VS POLRI DI SITUS VIVANEWS - Saepudin . (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
In 2015, there was a feud between two government institutions; KPK (Corruption Eradication Commission) and POLRI (Indonesian National Police) which got into a spotlight in society. There were various news reports from different perspectives and tones (neutral, negative, and positive) written about the feud. One of news website which reported about the feud is vivanews. This research aimed to analyse the feud between those institutions by using framing analysis. Using qualitative method to obtain the results, this research indicated that vivanews reported the facts of this case and added them with opinions about this case from various sources. Vivanews presented those institutions as ones that needed to be saved and asked the government to solve the feud to avoid a negative stigma toward the behavior of those institutions. The reality construction of mass media is not separated from three main aspects; internal and external of construction perperators, mass media communication system, and mass media construction strategy